Subjective beliefs among sport coaches about communication during practice - Moen, F.; Garland, K. (Scandinavian Sport Studies Forum, 2012)
This article looks at subjective beliefs among sport coaches in terms of what they consider to be effective communication during practice. A sample of 36 different opinions about different underlying aims for communication, and how this affects athletes` abilities to understand better (knowing), to perform better (doing), and/ or improve their focus, was presented to 23 sport coaches from different top level sports. A sample from a concourse of statements was presented to the coaches who were asked to consider the statements regarding what they thought are optimal communication during practice in action. The authors develop their analysis by employing the Q methodology. Four different factors emerged from the factor analysis, and one stronger factor had 18 cases when mixed cases were included. In general, coaches agree that during practice they must stimulate their athletes to be focused. In order to do this, their communication must be based on information and concepts that both coaches and athletes understand. Communication that effects common understanding and is based on clear and direct instructions seems to be beneficial to achieve a strong focus during action. The results also indicate that coaches must have conversations with their athletes in order to achieve common understanding, so that the information that is communicated during action is well discussed and clarified between themselves and their athletes